Flexibility of Older Adults Aged 55–86 Years and the Influence of Physical Activity - Liza Stathokostas; Matthew W. McDonald; Robert M. D. Little; Donald H. Paterson (Journal of Aging Research)
Cross-sectional age-related differences in flexibility of older adults aged 55–86 years of varying activity levels were examined. Shoulder abduction and hip flexion flexibility measurements were obtained from 436 individuals (205 men, 71±9 years; 231 women, 72±8 years). Total physical activity was assessed using the Minnesota Leisure-Time Physical Activity Questionnaire. Shoulder abduction showed a significant decline averaging 5 degrees/decade in men and 6 degrees/decade in women. Piecewise linear regression showed an accelerated decline in men starting at the age of 71 years of 0.80 degrees/year, whereas in women the onset of decline (0.74 degrees/year) was 63 years. Men and women showed a significant decline in hip flexion (men: 6 degrees/decade; women: 7 degrees/decade). Piecewise linear regression revealed a rate of decline of 1.16 degrees/year beginning at 71 years in men and in women a single linear decline of 0.66 degrees/year. Multiple regression analysis showed that age and physical activity accounted for only 9% of the variance in hip flexion in women and 10% in men, with age but not physical activity remaining significant. Similarly for shoulder abduction, age was significant but not physical activity, in a model that described 8% of the variance for both sexes.